2018
DOI: 10.3390/f9110705
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and Monitoring Protocols to Guarantee the Maintenance of Biodiversity in Certified Forests: A Case Study for FSC (Forest Stewardship Council) Forests in Southwestern Spain

Abstract: (1) Biodiversity, sustainable development and nature conservation are fundamental issues nowadays. All companies, administrations, governments and international organisations take these issues into consideration. Sustainable forest management always requires a compromise between profitability and conservation and in this fragile equilibrium, forest certification plays a key scheme. This sustainable management is of great importance in the European Union (EU), with the Forest Stewardship Council playing a funda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…In these cases, the analysis is carried out with several estimated dispersion distances [67]. It is also possible to test several distances in order to select the most suitable distance for the whole habitat [75]. However, the implementation of an analysis with a different set of distances makes the results difficult to apply and possibly unsuitable for managers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In these cases, the analysis is carried out with several estimated dispersion distances [67]. It is also possible to test several distances in order to select the most suitable distance for the whole habitat [75]. However, the implementation of an analysis with a different set of distances makes the results difficult to apply and possibly unsuitable for managers.…”
Section: Resultsmentioning
confidence: 99%
“…In these cases, dispersion distances should be adapted to other forest species. With respect to shrublands, it is also possible to develop a fragmentation status analysis as demonstrated for environmentally certified forests exploitation [75].…”
Section: Resultsmentioning
confidence: 99%
“…Although existing information in this field is quite scarce, a study conducted by Kurlavicius et al (2004) indicated that on average 17% of forests in the Baltic countries had a high conservation value for maintaining forest biodiversity. Nevertheless, even considering the Baltic countries, there is still a long way to go in preserving forests and promoting biodiversity despite the emergence of innovative pilot projects in this field (Hämäläinen, Strengbom, & Ranius, 2020;Sánchez-Almendro, Hidalgo, Galán, Carrasco, & López-Tirado, 2018). Currently, the main challenges related to the drastic reduction of biodiversity in forests are related to intensive agricultural practice, increasing urbanization, forest destruction, pollution, among other human factors (Vizzarri, Tognetti, & Marchetti, 2015).…”
Section: Performance In Specific Sdgsmentioning
confidence: 99%
“…Only a few studies addressed the role of forest certification in relation to N2000 (e.g. Sánchez-Almendro et al, 2018).…”
Section: Introductionmentioning
confidence: 99%